STRATEGI KEPEMIMPINAN KEPALA TATA USAHA DALAM MENDUKUNG PELAYANAN ADMINISTRASI DI SMAN 11 MUARO JAMBI - Rini, Eko Puspita; Sofyan, Sofyan; Saudagar, Ferdiaz (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to describe the leadership strategy of the head of administration in supporting administrative services at SMA Negeri 11 Muaro Jambi. The research focuses on leadership strategies, the administrative service process, obstacles encountered, and efforts to improve service quality. This study used a qualitative approach with a case study method. Data collection was conducted through observation, interviews, and documentation with informants consisting of the head of administration, administrative staff, principals, teachers, and students. The results indicate that leadership strategies are implemented through planning, implementation, and evaluation stages, supported by a clear division of tasks, the implementation of standard operating procedures (SOPs), and the use of information technology. Administrative services are running quite well, although there are still challenges such as limited human resources, infrastructure, and technical barriers. Efforts undertaken include optimizing the division of tasks, improving coordination, and developing staff competencies. Thus, leadership strategies play a crucial role in improving the effectiveness of administrative services.